Neutrophil-to-lymphocyte ratio predicts delirium after stroke. (5th July 2021) - Guldolf, Kaat; Vandervorst, Fenne; Gens, Robin; Ourtani, Anissa; Scheinok, Thomas; De Raedt, Sylvie
Abstract: Background: Delirium is an underdiagnosed and possibly preventable complication in acute stroke and is linked to poor outcome. Neutrophil-to-lymphocyte ratio (NLR), a marker of systemic inflammation, is also associated with poor outcome after acute ischemic stroke. Aim: To determine whether NLR is a predictor of post-stroke delirium (PSD). Methods: We reviewed the UZ Brussel stroke database and included 514 patients with acute ischemic stroke within 24 hours from stroke onset between February 2009 and December 2014. The presence of delirium was evaluated by two raters based on the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition criteria, using a retrospective chart review method. When no consensus was reached, a third evaluator was consulted. Patients were divided into two groups: those who developed delirium within the first week after stroke onset ( n = 201; 39%) and those who did not ( n = 313; 61%). Receiver operating characteristics (ROC) and multiple logistic regression analysis (MLRA) were used to identify predictors of PSD. Results: MLRA showed that NLR (odds ratio (OR) 1.14; 95% confidence interval (CI) 1.04–1.26), age (OR 1.05; 95% CI 1.03–1.07), National Institutes of Health Stroke Scale (NIHSS; OR 1.14; 95% CI 1.10–1.18), premorbid modified Rankin Scale (mRS) (OR 1.35; 95% CI 1.05–1.74) and premorbid cognitive dysfunction (OR 3.16; 95% CI 1.26–7.92) predicted PSD. ROC curve of a prediction model including NLR, age, NIHSS and premorbid cognitive dysfunction showed an area under the curve of 0.84 (95% CI = 0.81–0.88). Conclusions: Besides age, stroke severity, premorbid mRS and cognitive impairment, NLR is a predictor of PSD, even independent of the development of pneumonia or urinary tract infection.